Exploration of the roles of microbiota on biogenic amines formation during traditional fermentation of Scomber japonicus - Chen, Jingyi; Tang, Haiqing; Zhang, Mengsi; Sang, Shangyuan; Jia, Lingling; Ou, Changrong (Frontiers in Microbiology, 2022)
The influence of microbiota composition and metabolisms on the safety and quality of fermented fish products is attracting increasing attention. In this study, the total viable count (TVC), pH, total volatile base nitrogen (TVB-N) as well as biogenic amines (BAs) of traditional fermented Scomber japonicus (zaoyu) were quantitatively determined. To comprehend microbial community variation and predict their functions during fermentation, 16S rRNA-based high-throughput sequencing (HTS) and phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt) were employed, respectively. The fresh samples stored without fermentation were used as controls. TVC and TVB-N values increased rapidly, and the content of BAs exceeded the permissible limit on day 2 in the controls, indicating serious spoilage of the fish. In contrast, a slower increase in TVC and TVB-N was observed and the content of BAs was within the acceptable limit throughout the fermentation of zaoyu. Significant differences in microbiota composition were observed between zaoyu and the controls. The bacterial community composition of zaoyu was relatively simple and Lactobacillus was identified as the dominant microbial group. The accumulation of histamine was inhibited in zaoyu, which was positively correlated with the relative abundance of Vibrio, Enterobacter, Macrococcus, Weissella, et al. based on Redundancy analysis (RDA), while Lactobacillus showed a positive correlation with tyramine, cadaverine, and putrescine. Functional predictions, based on Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways analysis, revealed that the relative abundance of metabolic function exhibited a decreasing trend with prolonged fermentation time and the abundance of metabolism-related genes was relatively stable in the later stage of fermentation. Those metabolisms related to the formation of BAs like histidine metabolism and arginine metabolism were inhibited in zaoyu. This study has accompanied microbiota analysis and functional metabolism with the accumulation of BAs to trace their correspondences, clarifying the roles of microorganisms in the inhibition of BAs during fermentation of Scomber japonicus.